Human - robot swarm interaction for entertainment: from animation display to gesture based control - Alonso-Mora, Javier; Siegwart, Roland; Beardsley, Paul (HRI '14 : proceedings of the 2014 ACM/IEEE International Conference on Human-Robot Interaction : March 3-6, 2014, Bielefeld, Germany, 2014)
This work shows experimental results with three systems that take real-time user input to direct a robot swarm formed by tens of small robots. These are: real-time drawing, gesture based interaction with an RGB-D sensor and control via a hand-held tablet computer.